Plasminogen Activation at Low Temperatures in Plasma Samples Gontaining Therapeutic Concentrations of Tissue-Type Plasm i nogen Activator or Other Thrombolytic Agents - Rijken, D C; Seifried, E; Barrett-Bergshoeffi, M M; Dooijewaard, G (Thrombosis and Haemostasis, 1990)
It is known that in vitro plasminogen activation in blood samples taken during thrombolytic therapy with tissue-type plasminogen activator (t-PA) may lead to artefactually low fibrinogen and α2-antiplasmin values. To mimic this phenomenon, pooled normal plasma was supplemented with 2.5 μg/ml t-PA and incubated at various temperatures. The rates of fibrinogen degradation and α2-antiplasmin consumption were most pronounced at 37° C, were less pronounced at 25° C, but surprisingly, did not further decrease at 10° C, 0° C or −8° C. In contrast, when plasma was supplemented with 10° IU/ml urokinase or 30 IU/ml streptokinase, the rates of fibrinogen degradation and α2-antiplasmin consumption gradually decreased with incubation temperature and were negligible at 10° C and lower temperatures. The rate of plasminogen activation also decreased gradually with temperature in mixtures of purified fibrinogen, plasminogeo, α2- antiplasmin and t-PA. These results imply that, in a plasma milieu, additional factors with a stimulatory activity are involved in t-PA-induced plasminogen activation at around 0° C. The abnormally high reaction rate at low temperatures explains in vitro plasminogen activation observed during the processing of t-PA-containing blood samples.In contrast to the activation of plasminogen by t-PA, the slow inhibition of t-PA (2.5 μg/ml) by proteinase inhibitors in plasma could be minimized to a negligible level by keeping the plasma samples at 0° C. This makes it possible to reliably monitor t-PA activity during thrombolytic therapy